Type A Dissection in a Patient With Alport Syndrome. (December 2020) - Patel, Janki; Abt, Patrick; Cheng, Katarina; Aurigemma, Gerard; Rosenthal, Lawrence
Abstract : Supplemental Digital Content is available in the text.